Limit of $h_n(x)=x^{1+\frac{1}{2n-1}}$

$\lim_{n\to\infty}h_n(x) = x\lim_{n\to\infty}x^{\frac{1}{2n-1}}$ where $h_n(x)=x^{1+\frac{1}{2n-1}}$. I understand that $\lim_{n\to\infty}x^{\frac{1}{2n-1}}$ goes to one but what I don’t understand is how did our limit become $h_n(x)=|x|$? I’m just having hard time wrapping my head around the appearance of absolute value.

Note. This is an example (Chapter 6, Section 2) from Understanding Analysis by Abbott.

Solutions Collecting From Web of "Limit of $h_n(x)=x^{1+\frac{1}{2n-1}}$"

We have

$$\large x^{\large 1+\frac{1}{2n-1}}=x^{\large\frac{2n}{2n-1}}=\left(x^2\right)^{\large\frac{n}{2n-1}}\xrightarrow{n\to\infty}\sqrt{x^2}=\lvert x\rvert$$

Key point here is that there is $2n-1$ as the denominator. This is not by accident… It would not work with $2n$…

Let’s call $y_n=x^{\frac{1}{2n-1}}$

$y_n^{2n-1}=x$ has the same sign as $y_n$, since $2n-1$ is even.

For $x<0$, $y_n^{2n-1}=-|x|$, $\forall n \in \mathbb{N}$

$y_n$ can be written as (since it has the same sign as $y_n^{2n-1}):

$y_n=-|x|^{\frac{1}{2n-1}}$

$\lim_{n \to \infty} y_n=-1$

Thus

$\lim_{n \to \infty} |x|^{1+\frac{1}{2n-1}}=-x=|x|$

This solves the case $x<0$. The other case is obvious.